Aphid parasitoids (Hymenoptera: Braconidae, Aphidiinae) associated with pome and stone fruit trees in Iran - Ehsan Rakhshani (Journal of Crop Protection, 2012)
The aphidiine parasitoids (Hym., Braconidae) attacking the pest aphids on various pome and stone fruit trees in different parts of Iranwere studied. A total of 13 species belonging to seven genera of aphid parasitoids were identified in association with 17 aphid species on 10 different species of fruit trees. Sixty nine tritrophic associations were detected from the studied area of which 25 associations are newly recorded from Iran. An illustrated key is prepared for identification of the species. The parasitoids were categorized based on their potential impacts in biocontrol of pest aphids into the less important species and the key-stones. The first group of parasitoids includes the broadly oligophagous species, and even an occasional opportunistic species, Lysiphlebus fabarum (Marshall), while the second group includes the specific associations like Aphidius transcaspicus Telenga on Hyalopterus spp. and Pauesia antennata (Mukerji) on Pterochloroides persicae (Cholodkovsky). A probable occurrence of the univoltine aphid parasitoid, Pseudopauesia prunicola Halme in association with Ovatus insitus (Walker) is discussed.